Pengaruh Online Marketing, Dan E-Service Quality Terhadap Loyalitas Pelanggan Online Shop Yoya Outfit Malang - Wicaksono Deni Prasongko; Muhammad Ridwan Basalamah; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to describe the effects of online marketing and e-service quality on customer loyalty at the online shop Yoya Malang, both partially and together. The population is the Instagram followers of Yoya Outfit Malang's online shop consumers, totaling 276. There were a total of 73 samples collected. Respondents in this study were consumers of Yoya Outfit products who were selected through the purposive sampling method. Data testing techniques used in this study included validity testing, reliability testing, the classical assumption test, multiple linear regression analysis, hypothesis testing, and the coefficient of determination of the study. The results of this study indicate that the quality of online marketing electronic services has a simultaneous and partially significant effect on customer loyalty. Keywords: Online Marketing, E-Service Quality,Customer Loyalty